The clinical method: death and resurrection - Fidel Ilizástiguir Dupuy (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Considerations on the pertinence and prevalence of the clinical method defined as the process of diagnosis in the practice of human medicine is presented. Epistemologic considerations on the scientific nature of the clinical method, the medical taxonomy and the ''main types'' of differential diagnoses are commented. The process of diagnosis is analyzed from the perspective of logical processes, particularly from the hypothetic deductive method. Activation, refining and evaluation of hypothesis are emphasized as mechanisms of the diagnosis process. Some considerations on the impact of computing technology and its contributions to the clinical method being both benefited or not, are stated. Finally, the pertinence of a transformation of the clinical method due to the emergence of a more expansive and extensive medical paradigm is evaluated. This new paradigm will be hermeneuticaly based on the significance and understanding of the diagnosis, being men the central axis and medicine a humane science and a practice.